The Effect Of Mergers And Acquisitions On The Financial Performance Of Companies Listed On The Indonesia Stock Exchange - Buana, Sukma Genta; Santoso, Wahyu Purbo; Puri, Pustika Ayuning (Al-Makki Publisher, 2024)
Mergers and acquisitions (M&A) have become a common strategy in business development in today's global market. This study aims to analyze the effect of M&A on the financial performance of companies listed on the Indonesia Stock Exchange (IDX). Data is collected from companies that experienced M&A during a certain period, focusing on financial variables such as profitability, liquidity, leverage, and sales growth. The panel regression analysis method was used to test the research hypothesis. The results show that M&A has a significant influence on the financial performance of companies on the IDX. Specifically, the findings show an increase in profitability and sales growth after M&A, while liquidity tends to decrease in the short term after the transaction. Leverage may also fluctuate depending on the capital structure and financial policies the company implements post-M&A. This study provides valuable insights for stakeholders in the Indonesian capital market, including investors, fund managers, and regulators, to understand the implications of M&A on firms' financial performance. The practical implications of this study can assist firms in planning and evaluating their M&A decisions more carefully to increase firm value and reduce the risks associated with such transactions.